Current practice of external ventricular drainage: a survey among neurosurgical departments in Germany - Cinibulak, Zafer; Aschoff, Alfred; Apedjinou, Anani; Kaminsky, Jan; Trost, Hans A.; Krauss, Joachim K. (Acta neurochirurgica, 2016)
There are various recommendations, but no generally accepted guidelines, to reduce the risk of external ventricular drainage (EVD)-associated infections. The primary objective of the present study was to evaluate the current practice of EVD in a European country and to set the results in perspective to published data.
Gesehen am 04.05.2020